Baseline Inflammatory Biomarkers Identify Subgroups of HIV-Infected African Children With Differing Responses to Antiretroviral Therapy. (18th May 2016) - Prendergast, Andrew J.; Szubert, Alexander J.; Berejena, Chipo; Pimundu, Godfrey; Pala, Pietro; Shonhai, Annie; Musiime, Victor; Bwakura-Dangarembizi, Mutsa; Poulsom, Hannah; Hunter, Patricia; Musoke, Philippa; Kihembo, Macklyn; et al.
Abstract: Background.  Identifying determinants of morbidity and mortality may help target future interventions for human immunodeficiency virus (HIV)–infected children. Methods.  CD4 + T-cell count, HIV viral load, and levels of biomarkers (C-reactive protein, tumor necrosis factor α [TNF-α], interleukin 6 [IL-6], and soluble CD14) and interleukin 7 were measured at antiretroviral therapy (ART) initiation in the ARROW trial (case-cohort design). Cases were individuals who died, had new or recurrent World Health Organization clinical stage 4 events, or had poor immunological response to ART. Results.  There were 115 cases (54 died, 45 had World Health Organization clinical stage 4 events, and 49 had poor immunological response) and 485 controls. Before ART initiation, the median ages of cases and controls were 8.2 years (interquartile range [IQR], 4.4–11.4 years) and 5.8 years (IQR, 2.3–9.3 years), respectively, and the median percentages of lymphocytes expressing CD4 were 4% (IQR, 1%–9%) and 13% (IQR, 8%–18%), respectively. In multivariable logistic regression, cases had lower age-associated CD4 + T-cell count ratio (calculated as the ratio of the subject's CD4 + T-cell count to the count expected in healthy individuals of the same age; P < .0001) and higher IL-6 level ( P = .002) than controls. Clustering biomarkers and age-associated CD4 + and CD8 + T-cell count ratios identified 4 groups of children. Group 1 had the highest frequency of cases (41% cases; 16% died) and profound immunosuppression; group 2 had similar mortality (23% cases; 15% died), but children were younger, with less profound immunosuppression and high levels of inflammatory biomarkers and malnutrition; group 3 comprised young children with moderate immunosuppression, high TNF-α levels, and high age-associated CD8 + T-cell count ratios but lower frequencies of events (12% cases; 7% died); and group 4 comprised older children with low inflammatory biomarker levels, lower HIV viral loads, and good clinical outcomes (11% cases; 5% died). Conclusions.  While immunosuppression is the major determinant of poor outcomes during ART, baseline inflammation is an additional important factor, identifying a subgroup of young children with similar mortality. Antiinflammatory interventions may help improve outcomes.